Success Through Innovation, Reputation, and Location - Melanthiou, Yioula (My University, 2014)
Traditional communication methods are increasingly more expensive and more complex, and make it harder to reach target audiences. Companies are now requiring more value out of their promotional efforts steering the way for new methods to take center stage. Promotion using social media has come a long way and has now become an established option. The articles put together for this special issue mainly deal with matters relating to social media. Specifically, three papers discuss cultural impact and social networks, social network management, and web atmospherics. One of the papers also investigates the importance of company reputation and another reviews how success may be the outcome of a careful site location.